Interstellar medium properties and feedback in local AGN with the MAGNUM survey. Issue Volume 15:Issue S359(2020) (March 2019) - Mingozzi, M.; Cresci, G.; Venturi, G.; Marconi, A.; Mannucci, F.
Abstract: We investigated the interstellar medium (ISM) properties in the central regions of nearby Seyfert galaxies characterised by prominent conical or bi-conical outflows belonging to the MAGNUM survey by exploiting the unprecedented sensitivity, spatial and spectral coverage of the integral field spectrograph MUSE at the Very Large Telescope. We developed a novel approach based on the gas and stars kinematics to disentangle high-velocity gas in the outflow from gas in the disc to spatially track the differences in their ISM properties. This allowed us to reveal the presence of an ionisation structure within the extended outflows that can be interpreted with different photoionisation and shock conditions, and to trace tentative evidence of outflow-induced star formation ("positive" feedback) in a galaxy of the sample, Centaurus A.